Observing Umrah Worshipping Commitment with EMAI Model (Expectation, Motivation, Attitude, and Intention) among Middle-Class Muslims through Religiosity - Arham, M. Nur; Razak, Syaparuddin; Husain, Hukmiah; Sahaka, Arifin; Septiani, Nimas Ayu (Ijtimā iyya Journal of Muslim Society Research, 2025)
This study investigates the Umrah worshipping commitment of Middle-Class Muslims, focusing on Religiosity. Data from questionnaires, literature, documents, and secondary sources center on South Sulawesi's middle-class Muslims in Indonesia, with 213 respondents using a Likert scale. Structural Equation Modeling (SEM) via Smart PLS 4 analyzes the data, revealing a positive and significant correlation between Umrah worshipping intention and commitment. Attitude, Religiosity, Expectation, and Motivation positively influence Umrah worshipping intention. Attitude plays a pivotal role in shaping Umrah worshipping commitment through Intention mediation. Religiosity, Expectation, and Motivation impact Umrah worshipping intention through Attitude mediation. The study underscores religiosity in forming Umrah worshipping commitment via the EMAI Model, highlighting its foundational role. These insights provide a profound understanding of Umrah participation motivators, with strategic implications for sustainable policy and program development. The study contributes significantly to understanding Umrah worshipping intention and commitment determinants, guiding policy planning and community development strategies.